2022
DOI: 10.1080/10717544.2022.2152911
|View full text |Cite
|
Sign up to set email alerts
|

The nanoprodrug of polytemozolomide combines with MGMT siRNA to enhance the effect of temozolomide in glioma

Abstract: Temozolomide (TMZ) is a conventional chemotherapeutic drug for glioma, however, its clinical application and efficacy is severely restricted by its drug resistance properties. O6-methylguanine-DNA methyltransferase (MGMT) is a DNA repair enzyme, which can repair the DNA damage caused by TMZ. A large number of clinical data show that reducing the expression of MGMT can enhance the chemotherapeutic efficacy of TMZ. Therefore, in order to improve the resistance of glioma to TMZ, an angiopep-2 (A2) modified nanopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The efficacy of targeted modulation of signalling pathways was compared in two GB cell lines, U-251 MG and T98-G. These cell lines differ in expression levels of O6-methylguanine-DNA methyltransferase (MGMT), which contributes to the resistance of cells to drugs that act via DNA alkylation: U-251 MG expresses low levels of MGMT, while T98-G expresses higher levels of MGMT and is more resistant to alkylating agents 13 . We found that among the choice of screened compounds, the inhibitors of Aurora family possessed the highest potency.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of targeted modulation of signalling pathways was compared in two GB cell lines, U-251 MG and T98-G. These cell lines differ in expression levels of O6-methylguanine-DNA methyltransferase (MGMT), which contributes to the resistance of cells to drugs that act via DNA alkylation: U-251 MG expresses low levels of MGMT, while T98-G expresses higher levels of MGMT and is more resistant to alkylating agents 13 . We found that among the choice of screened compounds, the inhibitors of Aurora family possessed the highest potency.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most commonly occurring and malignant adult brain tumor ( Xu et al, 2023 ), and divided into ependymoma, astrocytoma [including glioblastomas (GBM)], oligodendroglioma, mixed glioma, and a few other tumors that vary widely in histology (from benign ependymoma to the most aggressive and lethal grade-IV GBM) ( Antin et al, 2020 ; Walsh et al, 2023 ). Despite multiple conventional therapy, including surgical resection, chemoradiotherapy and immunotherapy, glioma still possess a high recurrence and fatality rate ( Dong et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%